Pengaruh Reward Dan Punishment Terhadap Kinerja Karyawan PT. Surya Persada Sentosa Dengan Produktivitas Sebagai Variabel Intervening - Agus Basyari; Mudji Kuswinarno (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
This study takes an the property company, PT. Surya Persada Sentosa is one of the companies implementing a fairly strict reward and punishment system. This study uses a descriptive quantitative method with a survey of the respondents from employees of PT. Surya Persada Sentosa. The sampling technique uses simple random sampling method with 48 respondents which is analyzed using Path analysis. The results of this study are (1) Reward partially (individually) has a significant effect on the employee performance which can be seen at a significance value of t α, that is (0.001 0.05). (2) Punishment partially (individually) has a significant effect on employee performance which can be seen at (0.009 0.05). (3) Reward partially (individually) has a significant effect on productivity which can be seen a significance value of t α, which is (0,018 0.05). (4) Punishment partially (individually) has a significant effect on productivity with a significance value of t α, which is (0,032 0.05) (5) productivity partially (individually) has a significant effect on the employee performance that is (0.000 0.05). (6)Reward through productivity simultaneously (together) has a significant effect on employee performance which can be seen with a significance value of t α, that is (0,000 0.05 ) (6) Punishment through productivity simultaneously (together) has a significant effect on employee performance which is (21,228 2,82) with a significance value of t α, that is (0,000 0.05)